IMPROVING ENGLISH VOCABULARY MASTERY BY USING CROSSWORD PUZZLE - Wina Halimatus Sadiyah; Wina Septiani; Evie Kareviati (IKIP Siliwangi, 2019)
Vocabulary is important in English language. Because, to make a sentence an adequate vocabulary is needed. So, the researcher apply a method in the classroom which can make students motivated to learn vocabulary. The aim of the research is to know that the crossword puzzle is effective to improve students’ vocabulary or not through the use of crossword puzzles among seventh-grade students of MTs At-Taqwa Cihampelas in the academic year of 2018/2019. The method used in this research is quantitative technique and the pre-experimental research design conducted in one class. The population in this research is seventh-grade students of MTs At-Taqwa Cihampelas with the total number of the population are 104 students consisting of 3 classes, and the sample is class VII.A that consist of 30 students. The data is collected with the pretest and posttest as an instrument. The researcher conducted the tests before (pre-test) and after (post-test). After that the researcher give students a treatment consists of five meetings. The result show that the mean score of pre-test was 41.83, and the post-test was 75.67 after gives treatment uses crossword puzzle. It means that teaching English vocabulary using a crossword puzzle was effective media to improve students’ vocabulary at seventh-grade. Keywords: crossword puzzle, students’ vocabulary mastery.